2018
DOI: 10.1590/1678-7757-2017-0384
|View full text |Cite
|
Sign up to set email alerts
|

Study of the chemical interaction between a high-viscosity glass ionomer cement and dentin

Abstract: Objective To investigate the chemical interactions between a high-viscosity glass ionomer cement (GIC) (KetacTM Molar Easymix, 3M ESPE, Seefeld, Bavaria, Germany) and human dentin. It was also analyzed the dynamics of GIC setting mechanism based on the time intervals required for the GIC and the GIC mixed with dentin to achieve stability.Material and Methods Each constituent of GIC – powder (P) and liquid (L) – and powdered dentin (D), as well as the associations P+L, D+L, and P+L+D in the concentrations of 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…X-ray photoelectron spectroscopy is a high vacuum technique that does not allow clinically realistic conditions to prevail. However, more recently it has been confirmed that glass-ionomers undergo a chemical reaction with the mineral phase of teeth, using FTIR to study the reaction that occurs when ground tooth material was added to glass-ionomer dental cements [ 56 ]…”
Section: Ion-exchange Bonding To the Tooth Surfacementioning
confidence: 99%
“…X-ray photoelectron spectroscopy is a high vacuum technique that does not allow clinically realistic conditions to prevail. However, more recently it has been confirmed that glass-ionomers undergo a chemical reaction with the mineral phase of teeth, using FTIR to study the reaction that occurs when ground tooth material was added to glass-ionomer dental cements [ 56 ]…”
Section: Ion-exchange Bonding To the Tooth Surfacementioning
confidence: 99%
“…Study with Fourier transform infrared (FTIR) and Raman spectroscopy has shown that the setting time to achieve bond stability of GIC with dentin was longer for the high-viscosity GIC (38±7 min) than for the sample with 29% of GIC (28±4 min) [13]. In this work the matrix was maintained for both materials for 6 minutes and removed carefully.…”
Section: Discussionmentioning
confidence: 91%
“…Another aspect of extreme importance in the restorative technique is the time that must be waited until the initial hardening of the material to start finishing and expose GIC in contact with water [13]. Works on the ART technique do not mention the maintenance time [14,15] or when it is mentioned, it is below the setting time mentioned on the manufacturer's instructions [8,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamakami et al 6 recently proposed to analyze the dynamics of GIC setting mechanism based on the time intervals required for the GIC to achieve stability. The setting time or hardening time (in minutes) of a material presented in the package by the manufacturer is different from the time to reach complete reaction or chemical bonds stability (stabilization time) 6 . From the clinical point of view, this information is important because the time for stabilization of chemical bonds can influence mechanical properties of GICs and restoration longevity.…”
Section: Declaration Of Interestsmentioning
confidence: 99%